2021
DOI: 10.1186/s12981-021-00385-5
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access to HIV services during the COVID-19 pandemic—Nigeria, 2020

Abstract: Background To accelerate progress toward the UNAIDS 90-90-90 targets, US Centers for Disease Control and Prevention Nigeria country office (CDC Nigeria) initiated an Antiretroviral Treatment (ART) Surge in 2019 to identify and link 340,000 people living with HIV/AIDS (PLHIV) to ART. Coronavirus disease 2019 (COVID-19) threatened to interrupt ART Surge progress following the detection of the first case in Nigeria in February 2020. To overcome this disruption, CDC Nigeria designed and implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…14 Since 2019, Nigeria concurrently increased ART coverage, scaled up use of dolutegravir-based regimens, and expanded viral load monitoring, even during the COVID-19 pandemic. 15 17 Under the National ART Guidelines, 14 viral load monitoring is recommended at 6 months and 12 months after ART initiation and annually thereafter. People with virological non-suppression (≥1000 copies per mL) should repeat viral load testing 3 months after enhanced adherence counselling; patients with at least two consecutive tests indicating virological non-suppression should be reviewed for an ART regimen switch.…”
Section: Introductionmentioning
confidence: 99%
“…14 Since 2019, Nigeria concurrently increased ART coverage, scaled up use of dolutegravir-based regimens, and expanded viral load monitoring, even during the COVID-19 pandemic. 15 17 Under the National ART Guidelines, 14 viral load monitoring is recommended at 6 months and 12 months after ART initiation and annually thereafter. People with virological non-suppression (≥1000 copies per mL) should repeat viral load testing 3 months after enhanced adherence counselling; patients with at least two consecutive tests indicating virological non-suppression should be reviewed for an ART regimen switch.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a common finding in HIV projects among IDPs is that the absence of a structural service for HIV screening represents a major challenge for test delivery to all eligible people [ 30 ]. Thus, a reaction strategy to SARS-CoV2 outbreak, along with the implementation of COVID-19 mitigation initiatives, should entail the adaptation of existing services for delivering care for all the major causes of death and morbidity, including malnutrition and HIV-malaria coinfections [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complementing published experiences, 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 data were shared on service disruptions and mitigations in relation to HIV testing, antiretroviral therapy (ART), viral load testing, viral load suppression, pre-exposure prophylaxis (PrEP), prevention of vertical transmission, and voluntary medical male circumcision. Under-recognised factors that restricted HIV service delivery included staff shortages from illness, staff redeployment towards COVID-19, disruptions of public transportation services to travel to health facilities, and use of health facilities as isolation centers.…”
Section: Challenges To Service Deliverymentioning
confidence: 99%
“… 6 , 24 Data from Nigeria suggested that a focused effort on HIV testing and treatment, despite COVID-19, could result in rapid expansion of HIV testing and treatment. 14 , 25 Appropriately funded programmes, including those with important external funding, did better than programmes with less international support, particularly for key populations.…”
Section: How Hiv Services Adaptedmentioning
confidence: 99%